Planning As a Moral Discourse: Some Ideas For Planning Education in Indonesia - B. Setiawan (Journal of Regional and City Planning, 1996)
This  paper  questions the direction of planning education which is: 1) too oriented toward the practical interest of planning profession; 2) bas ed on the planning perception which is too deterministic and too emphasis on spatial aspect; 3) not fully perceive a more broader role   and  position  of  planning  in  general  public;  and  4)  ignoring  the  role  of  planning education as a place for developing planning science. Starting out from the conception that planning  is also a "moral discourse", this paper suggests a "holistic" planning education based  on  the  reality  that  the  thought  and  activity  of  planning  is  not  merely  a  technical rational  process,  but  fu ll  of  economic,  social,  and  political  complexities.  Begin  by evaluating and clarifying streams in planning theory, this paper then discusses the context and some ideas for the development of planning in developing countries as a whole and in Indonesia, in particular.